Screening of upland cotton genotypes (Gossypium hirsutum L.) against cotton verticillium (Verticillium dahliae Kleb.) Wilt (Bangladesh Journal of Botany, 2019)
Screening of upland cotton genotypes against Verticillium wilt disease was conducted. The 268 upland cotton genotypes (Carmen and Acala Maxxa cultivar were tolerant- control while cvs. Cukurova 1518 and Acala SJ2 were susceptible-control) were screened against defoliating (PYDV6) and non-defoliating (Vd11) pathotypes of the fungus in a randomized plot design with four replications in growth chamber. Field experiment was established according to the augmented experimental design. Variance analysis was significant (p ≤ 0.05) for all traits against Verticillium wilt. Cvs. Semerkant Uzbek and Taskent 6 were more tolerant than the tolerant-control cultivars against both pathotypes. Most of the genotypes were tolerant in field trial in terms of disease severity that was the lowest for STN K311 genotype in both periods. The highest seed cotton yield was obtained in genotypes as BA119, Okra 204, H-23, Gedera-5, PI 528420 and Acala Royale, which were moderately tolerant to the wilt disease.